Will oil prices decline over the long run? - Robert Kaufmann; Pavlos Karadeloglou; Filippo di Mauro (European Central Bank (ECB), 2008)
At present, oil markets appear to be behaving in a fashion similar to that in the late 1970s and early 1980s when oil prices rose sharply over an extended period. Furthermore, like at that time, analysts are split on whether such increases will persist or reverse, and if so by how much. The present paper argues that the similarities between the two episodes are not as strong as they might appear at first sight, and that the likelihood of sharp reversals in prices is not particularly great. There are a number of reasons in support of the view that it is unlikely that the first two decades of this century will mimic the last two decades of the previous century. First, oil demand is likely to grow significantly in line with strong economic growth in non-OECD countries. Second, on the supply side, OPEC is likely to enhance its control over markets over the next two decades, as supply increases in newly opened areas will only partially offset declining rates of production in other geologically mature non-OPEC oil regions. Moreover, while concerns about climate change will spur global efforts to reduce carbon emissions, these efforts are not expected to reduce oil demand. Finally, although there is much talk about alternative fuels, few of these are economically viable at the prices currently envisioned, and given the structural impediments, there is a reduced likelihood that the market will be able to generate sufficient quantities of these alternative fuels over the forecast horizon. The above factors imply that oil prices are likely to continue to exceed the USD 70 to USD 90 range over the long term.
Keywords: Q41; Q42; Q43; 330; Oil prices; Oil supply; Oil demand; Alternative fuels; Climate Change Policy; Ölpreis; Prognose; Ölmarkt; Ölpreis; Energiesubstitution; Internationale Umweltpolitik; Welt; OECD-Staaten; OPEC-Staaten